การพัฒนารูปแบบการจัดการเรียนการสอนตามแนวคิด Active Learning เพื่อเสริมสร้างทักษะและกระบวนการทางคณิตศาสตร์ สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 5 - Thammakul, Sasinapa (Journal of Graduate School Sakon Nakhon Rajabhat University, 2023)
The purposes of this research were to 1) develop the instructional model based on the active learning concept for enhancing mathematical skills and processes of Mathayomsuksa 5 students, 2) determine the efficiency of the developed instructional model, and 3) examine the effects after the implementation of the instructional model. The sample group, selected through cluster random sampling, consisted of 32 Mathayomsuksa students from class 5/1 at Sakhontawepee School in the second semester of the academic year 2020, using a classroom as a sampling unit. The research instruments comprised the instructional model, which involved handbooks for model implementation and lesson plans. Data collection involved a learning achievement test, an assessment test on mathematical skills and processes, and a set of questionnaires to evaluate students' satisfaction. The statistics for data analysis were percentage, mean, standard deviation, t-test Dependent Samples, and content analysis. The results revealed that: 1. The instructional model “5C Model” based on active learning for enhancing mathematical skills and processes for Mathayomsuksa 5 students comprising five elements: 1) Principles: The students engaged in learning by doing the activities and utilized a self-learning management system, fostering mathematical skills and processes to assist students with meaningful learning, self-confidence, awareness of learning’s importance, and connections to their daily life; 2) Objectives: The primary goal was to enhance the students’ mathematical skills and processes, 3) Instructional Processes comprising five stages: Stage 1: Challenge (C), Stage 2: Collaboration (C), Stage 3: Co-working (C), Stage 4: Conceptualization (C), and Stage 5: Creation (C); 4) Measurement and Evaluation involving the utilization of diverse authentic assessment methods; and 5) Learning Conducive Factors comprising two aspects: For teachers, ensuring they obtained correct concepts and understand how to conduct activities to enhance the mathematical skills and processes; For students, fostering responsibility and self–discipline. The efficiency of the developed instructional model was measured at 80.10/79.07. 2. The effectiveness of the instructional model revealed that: 2.1) The students’ learning achievement scores after the intervention were higher than those before the intervention, with a significance level of .01 (p<.01), 2.2) The students’ mathematical skills and processes demonstrated improvement after the intervention, 2.3) The students’ satisfaction with the instructional model was overall at a high level ( = 4.32, S.D. = 0.60) 3. The students’ progress in terms of mathematical skills and processes showed improvement.